Frontiers in Clinical Drug Research - Alzheimer Disorders: Volume 3 - Atta-ur-Rahman (Bentham Science Publishers, 2015)
Frontiers in Clinical Drug Research - Alzheimer Disorders is an e-Book series concerned with Alzheimer's disease (AD) that causes dementia, or loss of brain function. The disease affects the parts of the brain that deal with memory, thought, and language. Chapters in each volume focus on (Alzheimer Disorders) drug research with special emphasis on clinical trials, research on drugs in advanced stages of development and cure for Alzheimer’s disease and related disorders.Frontiers in Clinical Drug Research - Alzheimer Disorders will be of particular interest to readers interested in drug therapy of this specific neurodegenerative condition and related brain disorders as the series provides relevant reviews written by experts in field of Alzheimers Disease research.The third volume of this series features research on-perfusional modifications in prodromal Alzheimer's disease,-BACE inhibition treatment,-frontotemporal dementia caused by progranulin mutations-evidence-based treatment for psychological symptoms of Alzheimer’s Disease